Tumor neuroectodérmico primitivo - Larcos Andrade, Mónica Gabriela (2018)
A primitive neuroectodermal tumor (PPNET) or peripheral neuroepithelioma is a malignant neoplasm of small round blue cells derived from the neural crest. It is one of the most undifferentiated histological types among malignant tumors, because it is indistinguishable from Ewing’s sarcoma from the imaging and histology perspective. It considers a single pathology for this paper. It can appear in childhood or more frequently in adolescence; treatment includes chemotherapy, surgery, and radiation therapy. We present the clinical case of a 77-year-old patient who consulted for palpebral ptosis, and it classifies as Horner’s Syndrome. The final diagnosis was a peripheral neuroectodermal tumorconfirmed with histopathology and immunohistochemistry.